A review report on the mechanism of Trichoderma spp. as biological control agent of the basal stem rot - Syed Ali, Nusaibah; Musa, Habu (IntechOpen, 2019)
Trichoderma spp. have been the most common fungi applied as biological control agents (BCA) as an effort to combat a wide range of plant diseases. Its uses have recorded good success rate in controlling major plant diseases. Knowledge on the mechanisms employed by Trichoderma spp. could be further studied to improve its ability as an efficient biocontrol agent. The Trichoderma ability to curb plant diseases were mainly based on the activation of single or multiple control mechanisms. It is known that the Trichoderma-based biocontrol mechanisms mainly rely on mycoparasitism, production of antibiotic and/or hydrolytic enzymes, competition for nutrients, as well as induced plant resistance; numerous secondary metabolites produced by Trichoderma species could directly inhibit the growth of several plant pathogens. These mechanisms may act directly or indirectly against the targeted plant pathogen. This chapter reviews the recent updates on published research findings on mechanisms used by Trichoderma as biological control of plant diseases particularly on basal stem rot disease of oil palm caused by Ganoderma spp.